2020
DOI: 10.1177/1533317520904551
|View full text |Cite
|
Sign up to set email alerts
|

Disclosure of Amyloid Status for Risk of Alzheimer Disease to Cognitively Normal Research Participants With Subjective Cognitive Decline: A Longitudinal Study

Abstract: This study aimed to investigate the long-term impacts of disclosing amyloid status for a risk of Alzheimer disease (AD) to cognitively normal research participants with subjective cognitive decline (SCD), which represents an initial manifestation of AD. Forty-two participants were classified as the amyloid-positive ( n = 10) or amyloid-negative ( n = 32) groups. We assessed symptoms of anxiety, depression, and test-related distress at 6, 24, and 52 weeks after results disclosure. No difference was found over t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 52 publications
(76 reference statements)
1
28
0
Order By: Relevance
“…While there may be a transient increase in mild‐to‐moderate distress immediately after disclosure, 44 there appears to be a low risk of negative psychological outcomes over 3 to 6 months 45 . Studies in smaller populations have found no significant negative psychological sequelae among amyloid‐positive participants at 12 or 18 months, with 10 participants, 46 and 4 participants, 47 respectively. Recently a limited number of studies have proposed assessing the impact of communicating amyloid and APOE biomarker results together, 11,48 but the effects of disclosing multiple sources of risk on psychosocial outcomes are still unknown.…”
Section: What Is Known About Disclosure In Preclinical Ad?mentioning
confidence: 99%
See 1 more Smart Citation
“…While there may be a transient increase in mild‐to‐moderate distress immediately after disclosure, 44 there appears to be a low risk of negative psychological outcomes over 3 to 6 months 45 . Studies in smaller populations have found no significant negative psychological sequelae among amyloid‐positive participants at 12 or 18 months, with 10 participants, 46 and 4 participants, 47 respectively. Recently a limited number of studies have proposed assessing the impact of communicating amyloid and APOE biomarker results together, 11,48 but the effects of disclosing multiple sources of risk on psychosocial outcomes are still unknown.…”
Section: What Is Known About Disclosure In Preclinical Ad?mentioning
confidence: 99%
“…Research participants may differ in terms of motivation, risk tolerance, and psychological presentation. 45 Studies typically include participants over 65 years of age, with mean ages over 70, 45 , 46 and there is limited evidence about outcomes among younger individuals. Work with diverse groups to better anticipate those populations who may present to clinical practices in the future is critically important.…”
Section: How Can the Hd Framework Inform Research In Preclinical Ad?mentioning
confidence: 99%
“…Studies in smaller numbers of individuals with elevated amyloid levels support safety through 6 and 12 months. 26,28 In a nested qualitative study of a subset of participants in the A4 trial (50 with elevated amyloid levels and 30 with not elevated amyloid levels), however, approximately 20% of participants with elevated amyloid levels acknowledged considering suicide or physician-assisted death if they experience cognitive decline or become a burden to others. 31 These experiences emphasize the importance of the longitudinal evaluation of psychological outcomes being gathered in the A4 study.…”
Section: Elevated Amyloid Not Elevated Amyloidmentioning
confidence: 99%
“…Learning dementia risk information precipitates changes in health behaviors and future plans and raises concerns around stigma and discrimination. [7][8][9][10][11][12][13][14] This suggests the need to understand the preclinical AD experience of families as well, because family members share in AD dementia risk-whether directly due to shared risk factors or indirectly due to their likelihood of becoming caregivers. Moreover, family members may be asked to monitor the patient-in-waiting for changes in cognition and function or to engage in planning for the future.…”
Section: Introductionmentioning
confidence: 99%